Effects of nitrate and ammonium on growth and nitrogen partitioning in Guinea grass - Silveira, José Sebastião Machado; Sant'anna, Renato (Pesquisa Agropecuaria Brasileira, 2014)
Guinea grass plants (Panicum maximum, Jacq.), 19 days old, grown in culture solution in a glasshouse were treated for 96 hours with 100 ppm of nitrogen with the following proportion of NO-3/NH+4: 100/0, 75/25, 50/25, 25/75 and 0/100. The ammonium treatment in the diet caused a fall in the amounts of dry matter and nitrogen (total, soluble and insoluble of root system). Morphological alterations, characterized by short, large diameter, with few branches and brittle roots, appeared in ammonium rich treatments, indicating ammonium toxicity. In the aerial part of the plant, dry matter increased with the ammonium proportion up to the theoretical level of 65%, decreasing thereafter. The amounts of soluble nitrogen increased and the insoluble decreased, as the ammonium level in the diet increased immediately after 50%, suggesting disturb of protein metabolism. The largest nitrate accumulation occurred in the treatment 75/25. As the ammonium level in the diet increased there was a growing contribution of ammonium, aminoacids and unindentified N forms for the soluble N fraction, which became very large in the treatments 25/75 and 0/100. In the nitrato rich treatments, the main forms of N aminoacids were lisine, histidine, arginine, serine, alanine and the amides glutamine and asparagine while in the ammonium rich ones the two amides were by far the most important forms mainly asparagine.